A new method for online monitoring of boiling process in mini‐channels. Issue 4 (24th January 2019) - He, Yuchen; Ye, Xin; Ji, Haifeng; Huang, Zhiyao; Wang, Baoliang; Li, Haiqing
Abstract : A new method for online monitoring of boiling process, which is suitable for conductive fluids in mini‐channels, is proposed with the introduction of contactless conductivity detection (CCD) technique and perceptron algorithm (PA) technique. Series resonance principle and simulated inductor technique were adopted to develop a new CCD sensor. PA was used to implement the boiling stage identification, i.e., to identify the current stage was which stage of the boiling process. Three prototypes of the CCD sensors with inner diameters of 1.6, 2.0, and 2.5 mm were developed. With three kinds of conductive fluids (tap water, ethanol–tap water mixture, and KCl solution), boiling experiments were carried out. The experimental results show that the CCD sensor can effectively track the bubble growth of boiling process. The research results also indicate that the proposed method is effective and the identification accuracies are greater than 90.0%. © 2019 American Institute of Chemical Engineers AIChE J, 65: 1365–1375, 2019